ASPS Exhibits Anti‐Rheumatic Effects by Reprogramming Gut Microbiota and Increasing Serum γ‐Glutamylcysteine Level. Issue 3 (23rd November 2022) - Liu, Ang; Zhang, Min; Wu, Yanglin; Zhang, Chenhui; Zhang, Qin; Su, Xinlin; Zhu, Xu; Shi, Weidong; Liu, Jiangyun; Zhang, Yang; Huang, Cheng; Yan, Zhaowei; et al.
Abstract: Rheumatoid arthritis (RA) is an essential cause of labor loss and disability for people worldwide. Acanthopanax senticosus polysaccharide (ASPS) is one of the most important active components from A. senticosus, which exhibits various pharmacological activities such as antioxidation and immunomodulation. However, no studies have reported the application of ASPS in treating RA. This study aims to investigate the therapeutic effect of ASPS on RA and reveal its underlying mechanism. The potential therapeutic effect of ASPS against RA is initially verified in this study using the collagen‐induced arthritis model. Moreover, the protective benefits of ASPS are transmitted through the fecal microbiota and blocked by simultaneous antibiotic cocktail treatment, indicating that gut microbiota may be correlated with ASPS. The 16S rRNA sequencing using feces samples and untargeted UPLC‐MS metabolomics using serum samples further reveal that ASPS reprograms the arthritic progression triggered dysbiosis, enhances the expression of γ ‐glutamylcysteine (GGC) synthetase, and enriches the serum concentration of GGC. Furthermore, metabolites GGC is found to be able to effectively interrupt NLRP3 inflammasome activation via inhibiting ASC nucleation and therefore attenuate inflammatory arthritis. Taken together, this work highlights ASPS's therapeutic potential against RA, which mainly exhibits its effects via modulating gut microbiota and regulating GGC production. Abstract : Acanthopanax senticosus polysaccharide (ASPS) exhibits anti‐rheumatic effects by reprogramming gut microbiota and increasing serum γ ‐glutamylcysteine (GGC) level. ASPS reprograms gut microbiota and raises serum GGC concentration. Enrichment of GGC following the change of microbiota activates suppress arthritis via inhibiting NLRP3 inflammasome activation.